Risk Factors of Hypertension among Adults in Banyuwangi: A Case-Control Study - Aripin; Anak Agung Sagung Sawitri; Nyoman Adiputra (Universitas Udayana, 2015)
Background and purpose: Hypertension leads to an increase in vulnerability to heart and kidney disease as well as stroke. Although there are numerous studies regarding risk factors of hypertension, many of these are inconclusive. This study aimed to explore risk factors of hypertension among patients at Sempu Public Health Center, Banyuwangi. Methods: The study design was a case control with 158 samples consisting of 79 cases and 79 controls (1:1). Data were collected by interview using structured and IPAQ questionnaires, as well as through secondary data collated from medical records of patients. Subjects were selected using consecutive sampling technique over the period of February to April 2015. Data were analyzed using bivariate (chi-square test) to determine crude OR and multivariate (logistic regression) to calculate adjusted OR. Results: Multivariate analysis found that risk factors of hypertension were: low levels of physical activity (OR=24.89; 95%CI: 4.15-149.31), moderate stress (OR=19.72; 95%CI: 4.43-87.62) and heavy stress (OR=32.55; 95%CI: 3.92-270.07). High education levels (≥seniorhigh school-university) found to be protective towards hypertension (OR=0.16; 95%CI: 0.04-0.57). Tobacco use was not found as risk factor of hypertension (OR=0.58; 95%CI: 0.18-1.86). Conclusions: Low levels of physical activity, moderate stress and severe stress can increase the risk of hypertension of patients at Sempu Public Health Center, Banyuwangi.